Health-related quality-of-life results from the randomised phase II TAVAREC trial on temozolomide with or without bevacizumab in 1p/19q intact first-recurrence World Health Organization grade 2 and 3 glioma (European Organization for Research and Treatment of Cancer 26091) - Reijneveld, Jaap C.; Machingura, Abigirl; Coens, Corneel; Taphoorn, Martin J. B.; Taal, Walter; Clement, Paul M.; Idbaih, Ahmed; de Vos, Filip Y. F.; Klein, Martin; Wick, Wolfgang; Mulholland, Paul J.; Lewis, Joanne; et al. (European journal of cancer, 2023)
Background - In an international randomised controlled phase II study of temozolomide (TMZ) versus TMZ in combination with bevacizumab (BEV) in locally diagnosed non-1p/19q co-deleted World Health Organization grade 2 or 3 gliomas with a first and contrast-enhancing recurrence after initial radiotherapy, and overall survival at 12 months was not significantly different (61% in the TMZ arm and 55% in the TMZ + BEV arm). - Objectives - Health-related quality of life (HRQoL) was a key secondary end-point in this trial, and the main objective of this study was to determine the impact of the addition of BEV to TMZ on HRQoL. - Methods - HRQoL was assessed using the European Organization for Research and Treatment of Cancer QLQ-C30 (version 3) and QLQ-BN20 at baseline, and then every 12 weeks until disease progression. The pre-selected primary HRQoL end-point was the QLQ-C30 global health scale, with self-perceived cognitive functioning and pain selected as secondary HRQoL issues. Analysis was undertaken using linear mixed modelling and complemented with sensitivity analyses using summary statistics. A difference was considered clinically relevant with ≥10 points difference on a 100-point scale. - Results - Baseline compliance was high at 94% and remained above 60% until 72 weeks, limiting the analysis to 60 weeks. Compliance was similar in both arms. We found no statistically significant or clinically significant differences between the primary HRQoL end-point in both treatment arms (p = 0.2642). The sensitivity analyses confirmed this finding. The overall test for post-baseline differences between the two treatment arms also showed no statistically or clinically significant differences regarding the selected secondary end-point scales. - Interpretation - The addition of BEV to TMZ in this patient group neither improves nor negatively impacts HRQoL.
Online verfügbar: 19. Juni 2023, Artikelversion: 13. Juli 2023
Gesehen am 11.10.2023